Invasive Fungal Infections in Neonates in Canada: Epidemiology and Outcomes. Issue 11 (November 2018) - Ting, Joseph Y.; Roberts, Ashley; Synnes, Anne; Canning, Roderick; Bodani, Jaya; Monterossa, Luis; Shah, Prakesh S.
Abstract : Background: Neonatal fungemia is associated with adverse neonatal outcomes and higher overall healthcare expenditure. Our objective is to review the epidemiology of invasive fungal infections (IFIs) in neonates in Canada. Methods: A retrospective cohort study using data collected by the Canadian Neonatal Network (CNN) was conducted. Using a nested matched cohort study design, risk factors and outcomes of neonates born <33 weeks gestation (n = 39, 305) during 2003–2013 were compared between neonates diagnosed with an IFI during their stay to infection-free controls. Results: Overall incidence of IFI among all admitted neonates was 0.22% (n = 286), while the incidence of IFI in the group of neonates born <33 weeks gestation was 0.64%. Of the isolates, 170 (59%) had Candida albicans and 59 (21%) had Candida parapsilosis . Risk factors for IFI were lower gestation, male sex, Apgar score <7 at 5 minutes, higher severity of illness score, maternal diabetes and vaginal birth. Neonates with IFI had higher odds of mortality [adjusted odds ratio (aOR): 1.60; 95% confidence interval (CI): 1.06–2.43], necrotizing enterocolitis (aOR: 2.97; 95% CI: 1.76–5.01) and severe retinopathy of prematurity (aOR: 2.15; 95% CI: 1.26–3.67). Conclusions: The overall incidence of IFI in neonates was low in Canada in comparison to other large population cohort studies; however, the mortality and morbidity remained high. Abstract : Supplemental Digital Content is available in the text.